Diversity study and development of bee floral calendar for Kavrepalanchowk district, Nepal - Neupane, Bishnu Prasad; Chiluwal, Kashinath; Shrestha, Jiban (Journal of Agriculture and Natural Resources, 2024)
A purposive survey was carried out at Mandandeupur, Jyamdi, and Novobudda of Kavrepalanchowk for two consecutive years (January 2022-December 2023) to identify diversity of bee floral resources and to establish the floral calendar of honey bees in the district. A total of 153 plant species of 50 families were identified as floral resources in the district. Recorded flora was categorized into four groups; trees, shrubs, herbs and climbers. The highest category of bee flora grouped into tree (72 flora) followed by herbs (41), shrubs (30) and climbers (10 flora), respectively. The highest (104 plants) and the lowest (11 plants) number of flowering plants were observed during April and December, respectively. A sufficient number of flowering plants was noticed in March (93 plants), May (68 plants) and February (53 plants) of the spring season as well as during September (49 plants), October (44 plants) and November (41 plants) of the autumn season. From the total available flowering plants in the Kavrepalanchowk district, 90.84% of plants were sources of both nectar and pollen, while only 5.88% as pollen and the remaining 3.26% as sources of nectar only. To ensure sustainability, it is crucial to maintain the existing bee flora and so the floral calendar is important for effective honey production.